2006
DOI: 10.1523/jneurosci.4021-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Rod Phototransduction Machinery by Ciliary Neurotrophic Factor

Abstract: Ciliary neurotrophic factor (CNTF) promotes photoreceptor survival but also suppresses electroretinogram (ERG) responses. This has caused concerns about whether CNTF is detrimental to the function of photoreceptors because it is considered to be a potential treatment for retinal degenerative disorders. Here we report that the suppression of ERG responses is attributable to negative regulation of the phototransduction machinery in rod photoreceptors. Intravitreal injection of recombinant human CNTF protein in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 58 publications
7
85
0
Order By: Relevance
“…A paradigmatic example of gene supply is CNTF, which has been tested in a phase I safety trial (NCT00063765) by intraocular release in IR patients using encapsulatedcell implants (Sieving et al, 2006). Despite minor improvements in visual acuity in the absence of severe adverse effects, significant reductions in electroretinogram (ERG) were reported (Sieving et al, 2006), confirming what was previously observed in preclinical studies (Bok et al, 2002;Schlichtenbrede et al, 2003b;Wen et al, 2006). The detrimental effects observed following the intraocular delivery of high CNTF doses highlight the importance of regulating the expression of molecules with growth/neurotrophic/antiapoptotic activities, which may have tight therapeutic ranges.…”
supporting
confidence: 66%
“…A paradigmatic example of gene supply is CNTF, which has been tested in a phase I safety trial (NCT00063765) by intraocular release in IR patients using encapsulatedcell implants (Sieving et al, 2006). Despite minor improvements in visual acuity in the absence of severe adverse effects, significant reductions in electroretinogram (ERG) were reported (Sieving et al, 2006), confirming what was previously observed in preclinical studies (Bok et al, 2002;Schlichtenbrede et al, 2003b;Wen et al, 2006). The detrimental effects observed following the intraocular delivery of high CNTF doses highlight the importance of regulating the expression of molecules with growth/neurotrophic/antiapoptotic activities, which may have tight therapeutic ranges.…”
supporting
confidence: 66%
“…Although these cells are not true cones, they exhibit sufficient down-regulation of rodspecific genes to resist the deleterious effects of a rod-specific mutation. Interestingly, some of the rod gene expression changes induced by acute Nrl KO are similar to those seen following treatment of the retina with ciliary neurotrophic factor (CNTF) (47). This observation suggests that these two manipulations, acute Nrl KO and CNTF delivery, may preserve rod photoreceptors via a related pathway.…”
Section: Discussionmentioning
confidence: 78%
“…Molecular and cellular analyses have demonstrated that persistent CNTF-induced signaling alters the retinal transcriptome, including reduced expression of genes involved in phototransduction and severe suppression of cone opsins (25,28). However, single intravitreal injection of CNTF results in transient but reversible shortening of the photoreceptor outer segments and perturbation of phototransduction genes (29).…”
mentioning
confidence: 99%